Pengaruh Ukuran Perusahaan, Kualitas Audit Dan Profitabilitas Terhadap Kecepatan Waktu Dalam Penyampaian Laporan Keuangan - fitri dwi jayanti (Universitas Muhammadiyah Metro, 2018)
This research aimed to examine the influence of the which consists company size, audit quality and profitability on the speed submission of financial statements in the manufacturing companies listed on the Indonesia Stock Excange (IDX) in 2013 to 2015. Purposive sampling technique is used to obtain the sample size by 66 manufacturing or 198 data in three years. To analyze hyphotesis this research used logistic regression with SPSS version 21.The result of this study showed that audit quality variabels measured by Public Accountant Office big four and non big four received or influenced the speed submission of financial statements while the variable size of the company and profitability hypothesis rejected or variable does not affect the speed submission of financial statements. Keywords: Company Size, Quality of KAP, Profitability, the speed submission of financial statements